Extensible Hook System for Rendezvous and Docking of a CubeSat Swarm - Carlos Pérez-del-Pulgar; Antonio López Palomeque; Jesús Juli; Matteo Madi (Engineering Proceedings)
Deployment of CubeSat swarms is proposed for various missions necessitating cooperative interactions among satellites. Commonly, the cube swarm requires formation flight and even rendezvous and docking, which are very challenging tasks since they require more energy and the use of advanced guidance, navigation, and control techniques. In this paper, we propose the use of an extensible hook system and its corresponding GNC architecture to mitigate these drawbacks, i.e., it allows for saving fuel and reduces system complexity by including techniques that have been previously demonstrated on Earth. This system is based on a scissor boom structure, which could reach up to five meters for a 4U CubeSat dimension, including three degrees of freedom to place the end effector at any pose within the system workspace. We simulated the dynamic behavior of a CubeSat with the proposed system, demonstrating that the required power for a 16U CubeSat equipped with one extensible hook system is considered acceptable according to the current state-of-the-art actuators.